2012
DOI: 10.1016/j.eswa.2012.01.001
|View full text |Cite
|
Sign up to set email alerts
|

A multi-agent system for web-based risk management in small and medium business

Abstract: Business Intelligence has gained relevance during the last years to improve business decision making. However, there is still a growing need of developing innovative tools that can help small to medium sized enterprises to predict risky situations and manage inefficient activities. This article present a multiagent system especially conceived to detect risky situations and provide recommendations to the internal auditors of SMEs. The core of the multiagent system is a type of agent with advanced capacities for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 41 publications
0
28
0
2
Order By: Relevance
“…This procedure is similar to the one used for the mixture of experts [32,33]. The layer incorporates different statistical techniques based on linear programming [34], neural networks [32], and classifiers [34]. Thus, specialized agents in information fusion can combine different sensing technologies that provide heterogeneous data and provide more accurate information to the upper layer services.…”
Section: Proposed Architecturementioning
confidence: 99%
See 2 more Smart Citations
“…This procedure is similar to the one used for the mixture of experts [32,33]. The layer incorporates different statistical techniques based on linear programming [34], neural networks [32], and classifiers [34]. Thus, specialized agents in information fusion can combine different sensing technologies that provide heterogeneous data and provide more accurate information to the upper layer services.…”
Section: Proposed Architecturementioning
confidence: 99%
“…For this purpose, roles that allow merging information automatically through supervised learning and previous training are included. This procedure is similar to the one used for the mixture of experts [32,33]. The layer incorporates different statistical techniques based on linear programming [34], neural networks [32], and classifiers [34].…”
Section: Proposed Architecturementioning
confidence: 99%
See 1 more Smart Citation
“…Over the decades, CBR was widely applied in various areas such as medicine (El-Fakdi, Gamero, Meléndez, Auffret, & Haigron, 2014;Guessoum, Laskri, & Lieber, 2014;Ting, Wang, Kwok, Tsang, & Lee, 2010;Zhuang, Churilov, Burstein, & Sikaris, 2009), manufacturing industry (Kuo, 2010;Wu, Lo, & Hsu, 2008) and business (Carmona, Barbancho, Larios, & León, 2013;Li, Adeli, Sun, & Han, 2011), etc. It can been found that there are some studies on risk management based on CBR (Aarts, 1998;Bajo, Borrajo, De Paz, Corchado, & Pellicer, 2012;Chang, Ma, Song, & Gao, 2010;Dingwei & Xinping, 2011;Goh & Chua, 2009;Jung, Han, & Suh, 1999;Kumar & Viswanadham, 2007;Li, Yu, Zhou, & Cai, 2013;Lu, Li, & Xiao, 2013;Yao, Chen, & Yang, 2014). For example, Kumar and Viswanadham (2007) develop a CBR-based framework of the decision support system to support the risk management of construction supply chains.…”
Section: Introductionmentioning
confidence: 96%
“…The virtual organization of agents manages the resources of the Cloud system in which it is deployed. It was created with the PANGEA platform that facilitates the development of agents in light devices and the integration of different hardware [41,42]. The architecture is organized in 4 layers as can be seen in Figure 1 and that is what we briefly describe here for completeness [40].…”
Section: Previous Workmentioning
confidence: 99%